Winged leaf-cutting ants on nuptial flights used as transport by Attacobius spiders for dispersal - Ichinose, K.; Rinaldi, I; Forti, Luiz Carlos [UNESP] (Wiley-Blackwell, 2004)
1. Sexuals of a leaf-cutting ant, Atta bisphaerica Forel, left their nest for nuptial flights in October to December.2. When leaving a nest, 53 of the 479 winged sexuals (or alates) observed (11.1%) carried up to three inquiline spiders of Attacobius luederwaldti.3. Spiders exclusively selected winged sexuals, not workers, and preferred females, indicating their expectation of the stronger flight ability of females. Neither these sexuals nor workers that appeared out of the nest on flight days attempted to remove or attack spiders on the body of alates.4. New qucens landing from their nuptial flight did not carry spiders, indicating that the spiders had left the ants in the sky to be dispersed by wind.5. No spiders were found in more than 100 incipient nests, which were estimated to be 2-3 months old. This suggests that the spiders jumped off the alate during mid-flight and dispersed on the wind to inhabit larger nests.
Keywords: alate; ant; Atta; Attacobius; dispersal; leaf-cutting ant; nuptial flight; spider